2023
DOI: 10.3390/ijms241411691
|View full text |Cite
|
Sign up to set email alerts
|

The Involvement of Polyunsaturated Fatty Acids in Apoptosis Mechanisms and Their Implications in Cancer

Abstract: Cancer is a significant global public health issue and, despite advancements in detection and treatment, the prognosis remains poor. Cancer is a complex disease characterized by various hallmarks, including dysregulation in apoptotic cell death pathways. Apoptosis is a programmed cell death process that efficiently eliminates damaged cells. Several studies have indicated the involvement of polyunsaturated fatty acids (PUFAs) in apoptosis, including omega-3 PUFAs such as alpha-linolenic acid, docosahexaenoic ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 176 publications
0
11
0
Order By: Relevance
“…In this study, lipids from C. elegans were administered for the first time to human cancer models, and their anti-proliferative, anti-migratory, and stress-and cell deathinducing effects were observed. C. elegans was grown on industrial-grade glycerol, a byproduct of the food and soap industries, and in nitrogen-deprivation conditions, it accumulated polyunsaturated lipids rich in GLA, a molecule with well-established anticancer activity [11,54]. Previous publications have reported GLA's capability to suppress cell proliferation and induce apoptosis [55]; however, only one study has used microbial lipids (ML)s containing it, and observations have only been made on the leukemia cell line HL-60 [24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, lipids from C. elegans were administered for the first time to human cancer models, and their anti-proliferative, anti-migratory, and stress-and cell deathinducing effects were observed. C. elegans was grown on industrial-grade glycerol, a byproduct of the food and soap industries, and in nitrogen-deprivation conditions, it accumulated polyunsaturated lipids rich in GLA, a molecule with well-established anticancer activity [11,54]. Previous publications have reported GLA's capability to suppress cell proliferation and induce apoptosis [55]; however, only one study has used microbial lipids (ML)s containing it, and observations have only been made on the leukemia cell line HL-60 [24].…”
Section: Discussionmentioning
confidence: 99%
“…PUFAs are categorized into the ω-3 and the ω-6 families, with members from both families having been credited with potential cytotoxic activity against cancer cells. GLA is one of the strongest candidates of these FAs concerning the mentioned activity [10][11][12]. Proposed mechanisms of action vary; however, most findings suggest changes in the membranes' ability to facilitate their transporting roles [13] and the elevation of oxidative stress levels that can stimulate the intrinsic apoptosis pathways and finally lead to cell death [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…The preliminary explanation can only be given by considering previous studies. The anticancer effects of EPA are mainly attributed to its ability to modulate cell death pathways, inhibit cell proliferation and induce the expression of anti-in ammatory mediators [7,29]. The mechanism by which EPA promotes apoptosis alone involves the alteration of multiple complex cellular pathways; for example, EPA was able to induce cell cycle arrest in breast cancer cell lines [30].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that PUFAs act a vital role in the occurrence of malignant tumors, including the regulation of apoptosis [7,8]. Omega-3 PUFAs are one of the polysaturated fatty acids, that are mainly derived from deep-sea sh, such as sardines and herring, so they are also known as marine PUFAs [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation